PENDAMPINGAN PENGISIAN KEGIATAN SURVEY KONDISI IRGASI KE APLIKASI E-PAKSI - Andri Kurniawan; Ahmad Hidayawan; Annas Saiful Rohman (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Regional Governments in South Sumatra face difficulties in operating the E-PAKSI application for surveying irrigation conditions. This community service activity aims to enhance the capabilities of Water Resources Service personnel in South Sumatra Province, Musi Banyuasin Regency, and Banyuasin Regency in operating E-PAKSI. The method used was participatory Technical Guidance (Bimtek), with effectiveness measured via pre-test and post-test based on 14 criteria with a passing standard of 70-100. The theoretical foundation of this activity includes the Technology Acceptance Model (TAM) to ensure application acceptance and Participatory Action Research (PAR) as the basis for the collaborative mentoring method. The results showed a significant score increase; South Sumatra Province (70.5 to 100), Musi Banyuasin (61.75 to 100), and Banyuasin (63.5 to 100), thus all participants successfully exceeded the passing standard.